2020
DOI: 10.1177/0271678x20941263
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance assessment of the cerebral alterations associated with obesity development

Abstract: Obesity is a current threat to health care systems, affecting approximately 13% of the world’s adult population, and over 18% children and adolescents. The rise of obesity is fuelled by inadequate life style habits, as consumption of diets rich in fats and sugars which promote, additionally, the development of associated comorbidities. Obesity results from a neuroendocrine imbalance in the cerebral mechanisms controlling food intake and energy expenditure, including the hypothalamus and the reward and motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 147 publications
1
25
1
Order By: Relevance
“…However, two experimental animal studies have found that increased hypothalamic mIns-concentration is correlated with obesity and appetite behavior 49,50 . Our ndings obtained between BMI and hypothalamic Glc-concentration differ with the systematic review of Lizarbe et al, which reported a high glycemic concentration in brain tissue of animal models with high-fat diet consumption and obesity by using MRS 51 . One possibility that could explain these differences is that our sample size did not include clinically obese subjects or metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…However, two experimental animal studies have found that increased hypothalamic mIns-concentration is correlated with obesity and appetite behavior 49,50 . Our ndings obtained between BMI and hypothalamic Glc-concentration differ with the systematic review of Lizarbe et al, which reported a high glycemic concentration in brain tissue of animal models with high-fat diet consumption and obesity by using MRS 51 . One possibility that could explain these differences is that our sample size did not include clinically obese subjects or metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…In this context, MRI methods have been recently reviewed to be helpful for the characterization of the physio-pathological processes in the brain associated with obesity development. 19 As a consequence of a potential reduction of CBF, we hypothesize further that HFD feeding leads to changes in behavior and TEL treatment can prevent these changes since there are studies which show that ARB have beneficial effects in Alzheimer’s disease. 20,21 Therefore, we used different tests that address memory and anxiety-like behavior.…”
Section: Introductionmentioning
confidence: 97%
“… 1 , 5 With respect to the hypothalamus, no consistent structural hypothalamic abnormalities have been established in association with obesity in general, although its involvement in the functional networks of food intake and energy metabolism is beyond all doubt. 20 A multiparametric MRI study demonstrated a relation between BMI and higher proton diffusivity in the hypothalamus but also not with hypothalamic total volume. 21 On the contrary, in systemic diseases which are associated with substantial metabolic alterations, body weight loss due to hypermetabolism, and/or reduced food intake has been demonstrated to be associated with hypothalamic atrophy, for example, in neurodegenerative diseases like amyotrophic lateral sclerosis 13 or Huntington’s disease 22 and in anorexia nervosa.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future studies will have to use correlational analyses with fluid hormonal markers like leptin, somatostatin, and hormones of androgen metabolism together with advanced structural and functional neuroimaging techniques which allow for more detailed differentiation of hypothalamic subunits and target the hypothalamic connectivity. 20 , 21 , 23 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%